Real time dose rate measurements with fiber optic probes based on the RL and OSL of beryllium oxide. (July 2016) - Teichmann, T.; Sponner, J.; Jakobi, Ch.; Henniger, J.
Abstract: This work covers the examination of fiber optical probes based on the radioluminescence and real time optically stimulated luminescence of beryllium oxide. Experiments are carried out to determine the fundamental dosimetric and temporal properties of the system and evaluate its suitability for dose rate measurements in brachytherapy and other applications using non-pulsed radiation fields. For this purpose the responses of the radioluminescence and optically stimulated luminescence signal have been investigated in the dose rate range of 20 mGy/h to 3.6 Gy/h and for doses of 1 mGy up to 6 Gy. Furthermore, a new, efficient analysis procedure, the double phase reference summing, is introduced, leading to a real time optically stimulated luminescence signal. This method allows a complete compensation of the stem effect during the measurement. In contrast to previous works, the stimulation of the 1 mm cylindrical beryllium oxide detectors is performed with a symmetric function during irradiation. The investigated dose rates range from 0.3 to 3.6 Gy/h. The real time optically stimulated luminescence signal of beryllium oxide shows a dependency on both the dose rate and the applied dose. To overcome the problem of dose dependency, further experiments using higher stimulation intensities have to follow. Highlights: RL and OSL measurements with BeO extended to low dose (rate) range. A new method to obtain the real time OSL: Dual Phase Reference Summing. Real time OSL signal shows both dose and dose rate dependency. Real time OSL enables a complete discrimination of the stem effect.